Answer:
The solutions are:
x1 = (-1/2)(5 + 3i)
and
x2 = (1/2)(11 + 5i)
Explanation:
Given the equations:
ix1 + x2 = 4 .................................(1)
2x1 + (1 − i)x2 = 3i ......................(2)
From (1), make x2 the subject, to have:
x2 = 4 - ix1 ...................................(3)
Using (3) in (2)
2x1 + (1 - i)(4 - ix1) = 3i
2x1 + 4 - ix1 - 4i + i²x1 = 3i
2x1 + 4 - ix1 - 4i - x1 = 3i
(because i² = -1)
(2 - i - 1)x1 + 4(1 - i) = 3i
(1 - i)x1 + 4(1 - i) = 3i
Divide both sides by (1 - i)
x1 + 4 = 3i/(1 - i)
Multiply both the numerator and denominator of the right hand side by the conjugate of (1 - i). The conjugate of (1 - i) is (1 + i), the aim of this multiplication is to makes the denominator a real number, rather than complex.
x1 + 4 = 3i(1 + i)/(1 - i)(1 + i)
x1 + 4 = (3i - 3)/2
x1 = (3/2)(i - 1) - 4
= [3(1 -i) - 8]/2
= (3 - 3i - 8)/2
= (-5 - 3i)/2
x1 = (-1/2)(5 + 3i)..............................(4)
Using this in (3)
x2 = 4 - ix1
x2 = 4 - i(-1/2)(5 + 3i)
= 4 + (1/2)(5i - 3)
= (8 + 5i + 3)/2
= (11 + 5i)/2
x2 = (1/2)(11 + 5i)